Referral route: a determinant of inequity for children with undiagnosed genetic diseases? - Tang, Zeyu; Mis, Emily K.; Lakhani, Saquib A. (Frontiers in Genetics, 2026)
Individuals with rare genetic diseases collectively comprise 3.5%–5.9% of the population, roughly 400 million people worldwide. Undiagnosed rare disease programs have leveraged next-generation sequencing technologies to facilitate genetic diagnoses, thereby shortening the complex diagnostic odysseys that many of these patients and their families endure. However, enrollment data suggest disparities in access to undiagnosed genetic disease programs among racial and ethnic minorities. To better understand this issue, we conducted a retrospective review of our rare undiagnosed disease program to assess whether referral route was a determinant of disparities for minoritized racial and ethnic communities. Participants enrolled in the Yale Pediatric Genomics Discovery Program from 2016 to 2022 were self-categorized into four racial and ethnic groups: Hispanic/Latinx (any race), non-Hispanic White, non-Hispanic Black/African American, non-Hispanic Other. Route of referral was classified as Inpatient, Outpatient, or Outside/Self referrals. Completion rates were the percentage of participants who completed enrollment compared to their respective group. Demographics for program participants were different from Yale-New Haven Children’s Hospital demographics, with over-representation of non-Hispanics Whites. Direct inpatient recruitment had a higher yield of Hispanic individuals, which was offset by under-representation of minoritized individuals in the Outside/Self setting. Inpatients had lower referral completion rates compared to Outpatient and Outside/Self referrals. These data suggest that the route of referral may represent different levels of access to care, and inpatient recruitment may be leveraged to promote participation by some minoritized communities. We encourage other programs to examine their cohorts for representation and identify strategies for improving participation.